A Clinical Survey of Tinea Suspected Patients for Dermatophytes and Related Fungal Agents - Awasthi, Prerna (International Journal of Pharmaceutical & Biological Archive, 2015)
A Clinical Survey of Tinea Suspected Patients for Dermatophytes and Related Fungal Agents